The uses of moral talk: Why do managers talk ethics? - Bird, Frederick (Journal of business ethics, 1989)
When managers use moral expressions in their communications, they do so for several, sometimes contradictory reasons. Based upon analyses of interviews with managers, this article examines seven distinctive uses of moral talk, sub-divided into three groupings: (1) managers use moral talk functionally to clarify issues, to propose and criticize moral justifications, and to cite relevant norms; (2) managers also use moral talk functionally to praise and to blame as well as to defend and criticize structures of authority; finally (3) managers use moral talk dysfunctionally to rationalize morally ambiguous behavior and to express frustrations. The article concludes with several practical recommendations.